A suite of macrophyte species distribution models for investigating hydrology-driven spatial changes in a large flood-pulsed tropical wetland. Issue 2 (4th May 2019) - Murray-Hudson, Michael; Wolski, Piotr; Brown, Mark T.; Davidson, Thomas
ABSTRACT: Spatial ecological models of wetland systems are important tools for evaluating system response to changes in hydrological inputs, arising from anthropogenic manipulation or climate change. We present an approach using multiple species distribution models (SDMs) for floodplain macrophytes, based on empirical relationships with flood duration. 27 indicator species were identified for four floodplain classes in a seasonally pulsed distributary of the Okavango Delta, based on data from a field survey of 30 floodplain sites. Spatial hydrological history was constructed using a combination of Landsat and MODIS imagery, and ground-truthing. Relationships between duration and occurrence were used to construct general linear probability models (GLMs) of species along the hydroperiod gradient. The GLM parameters were then used to construct SDMs driven by a spatial hydrological model, which generates annual assessments of inundation duration in months in each 1km 2 cell across the Delta. The modelled distribution fits were mostly robust (18 GLMs had p  < 0.05). Tests of model performance against a validation set of five floodplain sites showed an average of 87% correct predictions of presence. The strong performance of the models and the ability to produce map-based and quantitative output indicate good potential for use in assessment of basin development scenarios.